2014
DOI: 10.1016/j.jcf.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ivacaftor on CFTR forms with missense mutations associated with defects in protein processing or function

Abstract: These in vitro data indicated that ivacaftor is a broad acting CFTR potentiator and could be used to help stratify patients with CF who have different CFTR genotypes for studies investigating the potential clinical benefit of ivacaftor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
344
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(382 citation statements)
references
References 26 publications
33
344
3
2
Order By: Relevance
“…32 In Fisher rat thyroid cells G551D showed 1% of wild-type function, and human bronchial epithelial cells generated from G551D/F508del lung explants expressed 5% wild-type CFTR function. 24 Our results suggest that, in contrast to classes I and II, class III CFTR mutations confer sufficient chloride channel function to maintain early intestinal fluid homeostasis and thus eliminate the risk for MI in patients with CF.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…32 In Fisher rat thyroid cells G551D showed 1% of wild-type function, and human bronchial epithelial cells generated from G551D/F508del lung explants expressed 5% wild-type CFTR function. 24 Our results suggest that, in contrast to classes I and II, class III CFTR mutations confer sufficient chloride channel function to maintain early intestinal fluid homeostasis and thus eliminate the risk for MI in patients with CF.…”
Section: Discussionmentioning
confidence: 64%
“…While non-CFTR modifier genes as well as environmental factors largely influence the development and progression of lung disease and nutritional decline, [33][34][35][36] we demonstrate that the severity of the underlying CFTR genotype 24 for the major and missense cystic fibrosis-causing variants for which patient group size was ≥10 in at least the US group. itself plays a role in predisposing patients to an overall better or worse clinical outcome measured as lung function and nutritional status.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The CFTR potentiator creates opportunities for personalised medicine for CF However, because the G551D mutation affects only ,4% of CF patients worldwide, considerable challenges remain that need to be overcome before a larger group of patients can benefit from these novel CFTR modulator therapies. In this context, recent in vitro studies demonstrated that ivacaftor can improve the open probability and, thus, potentiate other non-G551D gating mutations, as well as other rare CFTR mutations that cause mild defects in processing and/or conductance [74,75]. These results indicate that ivacaftor may be more broadly acting and beneficial for a larger group of CF patients that carry CFTR mutations with residual function, including pancreatic-sufficient patients.…”
Section: Emerging Novel Therapies To Rescue Mutant Cftr: Breakthroughmentioning
confidence: 94%
“…While both drugs are assumed to directly bind to mutant and wild-type CFTR, lumacaftor has been shown to stabilize the NBD1/MSDs interface in CFTR variants both in the ER and the PM [108,109]. In contrast, ivacaftor can stimulate the gating of several missense mutations with impaired channel activation upon PKA-mediated phosphorylation [110]. Thus, lumacaftor and ivacaftor may have the potential to revert the conformational and functional defects, respectively, of the ethanol-induced dysfunctional CFTR, a scenario that has to be evaluated experimentally in the future.…”
mentioning
confidence: 99%